Secondary effects of urban heat island mitigation measures on air quality. (January 2016) - Fallmann, Joachim; Forkel, Renate; Emeis, Stefan
Abstract: This study presents numerical simulations analysing the effect of urban heat island (UHI) mitigation measures on the chemical composition of the urban atmosphere. The mesoscale chemical transport model WRF-Chem is used to investigate the impact of urban greening and highly reflective surfaces on the concentrations of primary (CO, NO) as well as secondary pollutants (O3 ) inside the urban canopy. In order to account for the sub-grid scale heterogeneity of urban areas, a multi-layer urban canopy model is coupled to WRF-Chem. Using this canopy model at its full extend requires the introduction of several urban land use classes in WRF-Chem. The urban area of Stuttgart serves as a test bed for the modelling of a case scenario of the 2003 European Heat Wave. The selected mitigation measures are able to reduce the urban temperature by about 1 K and the mean ozone concentration by 5–8%. Model results however document also negative secondary effects on urban air quality, which are closely related to a decrease of vertical mixing in the urban boundary layer. An increase of primary pollutants NO and CO by 5–25% can be observed. In addition, highly reflective surfaces can increase peak ozone concentration by up to 12% due to a high intensity of reflected shortwave radiation accelerating photochemical reactions. Graphical abstract: Highlights: We model impacts of urban heat island mitigation measures on air quality. Liaison of a multi-layer urban canopy model and WRF-Chem. Urban greening and white roofs decrease average ozone concentration. We find an increase of primary pollutants due to reduced vertical mixing. Peak ozone concentration increases for white roofs due to short-wave reflection.